2009
DOI: 10.1026/0049-8637.41.4.181
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor experience influences the spatial cognitive development of infants with Spina Bifida

Abstract: Abstract. This study tested the hypothesis, derived from studies of normal infants, that experience with self-produced locomotion facilitates the development of two important spatial cognitive skills: a two-position object permanence manual search task, and a task assessing the infant’s following of the point/gaze gesture of the experimenter. Both of these tasks, as assessed in these studies, show median ages of onset between 7 and 9 months in normal infants, but very recent studies with normals have shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 22 publications
4
26
3
1
Order By: Relevance
“…The second paradigm assessed the ability to follow the point and gaze gesture of an experimenter and the third paradigm assessed the ability to extract the invariant form of an object that was presented in multiple sizes, orientations, and colors. Consistent with the Campos et al (2009) findings, the infants showed marked improvements on each of the spatial-cognitive paradigms following the acquisition of crawling, which occurred at an average age of 19.6 months, well after typically-developing infants begin to crawl. In addition, we have also noted already that infants who engage in effortful forms of locomotion, like belly crawling, don't appear to profit, in terms of psychological consequences, from their locomotor experience.…”
Section: What Implications Do Motor Disabilities Have For Psychologicsupporting
confidence: 87%
See 2 more Smart Citations
“…The second paradigm assessed the ability to follow the point and gaze gesture of an experimenter and the third paradigm assessed the ability to extract the invariant form of an object that was presented in multiple sizes, orientations, and colors. Consistent with the Campos et al (2009) findings, the infants showed marked improvements on each of the spatial-cognitive paradigms following the acquisition of crawling, which occurred at an average age of 19.6 months, well after typically-developing infants begin to crawl. In addition, we have also noted already that infants who engage in effortful forms of locomotion, like belly crawling, don't appear to profit, in terms of psychological consequences, from their locomotor experience.…”
Section: What Implications Do Motor Disabilities Have For Psychologicsupporting
confidence: 87%
“…The relation has also been confirmed in a longitudinal study of seven infants with spina bifida (Campos et al, 2009). Spina bifida is a neural tube defect that is associated with delays in locomotor and psychological development.…”
Section: Locomotor Experience and Manual Search For Hidden Objectsmentioning
confidence: 67%
See 1 more Smart Citation
“…To date, only a few studies have examined populations at risk for motor delays, but they generally indicate that these links are robust in the face of early delays. Thus, for example, in a study of a group of infants with Spina Bifida between the ages of 8.5 and 13.5 months, relations were observed between prone progression and communication similar to those identified in work with TD infants (Campos, Anderson, & Telzrow, 2009), and overall delays in language in children with Spina Bifida relative to TD infants have been reported from 6 – 36 months (Lomax-Bream et al, 2007). A study by Suttora & Salerni (2012) with preterm infants is the only other study examining such links.…”
Section: Introductionmentioning
confidence: 55%
“…Several studies have shown that locomotor experiences facilitate the development of joint attention skills in typically developing infants (e.g., Campos, Kermoian, Witherington, Chen, & Dong, ; Tao & Dong, ) suggesting major implications for infants with locomotor delay. Until now, only few studies tested the consequences of the link between joint attention skills and locomotor experiences in infants with locomotor delay due to spina bifida myelomeningocele and revealed deficits in joint attention skills in those infants (Campos, Anderson, & Telzrow, ; Rivera, ). However, infants with spina bifida did not only suffer from motor impairments, they also showed deficits in cognitive, language, and daily living skills (Lomax‐Bream et al, ; Lomax‐Bream, Barnes, Copeland, Taylor, & Landry, ).…”
Section: Introductionmentioning
confidence: 99%